Terrorism Risk and Democratic Preferences in Pakistan - Faiz Ur Rehman; Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
Beyond direct damages, terrorism creates fear and insecurity, potentially reducing support for democratic institutions if these are deemed inadequate to tackle the threat, and increasing support for military governments. To investigate this possibility, we use data from Pakistan, a country that experienced an exponential rise in terrorism since 2001. Exploiting individual level data on democratic attitudes and district level information on terrorist attacks, we document that persistent exposure to terrorism (and more broadly to violence) is associated to a significantly lower support for democratic values. Results are robust to the inclusion of different sets of controls, to sample splits based on gender, urbanization and education, and to endogeneity considerations. Instrumenting terrorism and violence by the distance from the Pak-Afghan border and by religious fractionalization suggests that the documented correlation reflects a causal impact. Terrorism thus threatens not only individuals, but also democratic institutions.
Keywords: D74; F59; K42; O17; 330